Literatur review: Implementasi Marketing Mix 7P Terhadap Tingkat Kepuasan Pasien Di Rumah Sakit - Desi Natalia Marpaung; Ernawaty - Ernawaty; Diansanto - Prayoga; Syifa’ul - Lailiyah (VISIKES: Jurnal Kesehatan Masyarakat, 2021)
The marketing mix is a marketing strategy used by hospitals to maximize service delivery to patients. The purpose of  study was to analyze the effect of the 7P marketing mix (product, price, place, promotion, process, people, physical building) on patient satisfaction in the hospital. The method of writing literature review begins with selecting topics, determining keywords to find journal references. The databases used include Google Scholar, Elsevier, Portal Garuda, Shinta. Reference searches are limited from 2016 to 2020. The keywords used are "Marketing mix, 7p Marketing mix, Hospital, Patient Satisfaction". This study sought a reference list of studies, which included 85 studies taken from the search. A total of 25 articles in cleaning and there are 7 articles included in the discussion. Selection of journals selected based on inclusion criteria. The inclusion criteria in this research  is an analysis of the effect of 7P Marketing Mix on Patient Satisfaction  in the Hospital. Of the 7 studies reviewed, one study explained that the 7P marketing mix had a significant effect on patient satisfaction as evidenced by statistical tests with p value = 0.00 <? = 0.05. Through 7P marketing optimization in the hospital, it will have a positive impact on increasing patient satisfaction  Keywords :  Hospital, Marketing Mix, Marketing Mix 7P, Patient Satisfaction